Prioritizing and spending of local government units, national government agencies, donor agencies and private institutions on capacity development: Final research report - GenTwoFifteeen Development Foundation Inc. (Philippines) (Animo Repository, 2010)
Capacity development is a process by which individuals, groups, organizations, institutions and societies foster: a) decentralized governance, and b) convergence towards self-reliant and autonomous local authorities and active partners for national development (CapDev Agenda in a Nutshell, 2009). Capacity development activities of the local government units (LGUs) in the Philippines are relevant to the national development goals of the country. However, there is no overall comprehensive monitoring and evaluation system to track the cumulative results of capacity development in the local government units (LGUs). The performance of the LGUs in the development of their capacities, their prioritization, patterns of spending, drivers and capacity needs are looked into this study. The study made use of questionnaires as guide during individual or group interviews involving respondents from sampled provincial, city and municipal LGUs from Luzon, Visayas and Mindanao re-presenting different income classification and geographical distribution. Representatives from the donor agencies and national government agencies were also included as respondents in the study. Respondents have shown varied levels of understanding of the concept of capacity development. This understanding is reflected in the focus CapDev activities implemented. The LGU CapDev initiatives are focused on the enhancement of competencies in the individual and organizational levels along the managerial, professional and technical skills. These are supported by the LGU's general funds and the 20% development fund. Identifying capacities for prioritization, as a process practiced by LGUs, is challenged with the need for development of ownership and commitment to change from those who have the leadership responsibility and influence. The use of self-assessment tools such as the Local Governance Performance Monitoring System (LGPMS) and Systems on Competency Assessment for Local Governments (SCALOG) showed to be a facilitating method for the formulation of the LGU's CapDev agenda. Prioritization of CapDev activities considered then needs and relevance of these training and other CapDev activities to their needs as articulated in their strategic commitments for development, availability of resources, policy environment, political leadership and support, and partnership with NGAs, local research institutions and donor organizations. Challenges met by these LGUs in the implementation of CapDev activities include budget, personnel, training requirements and logistical limitations. Not all the sampled LGUs possess a defined and formulated CapDev Agenda. The need for a formulated and defined CapDev agenda is important alongside human resource management plan. This ensues that the well-trained human resources are place to effective use and sustained. The collective involvment of the network of community organizations, LRIs, NGOs, NGAs provided greater capacity. However, capacity development of LGUs during the period being studies has yet to address issues central to social, economic, and environmental development. It has often been absorbed by short-term concerns. Diversification of CapDev implementation for the participation of a broad base of stakeholders is needed as well as skills in peace making and peace building, and for institutional and policy reforms to support the broader peace process particularly in Mindanao.